Influence of nutridense low phytate corn and added fat on growing-finishing pig growth performance - Linneen, S.K.; Gottlob, R.O.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two studies were conducted to evaluate the effect of NutriDense Low Phytate corn in conjunction with increasing amounts of added fat on growing and finishing pig performance. NutriDense Low Phytate corn is similar to NutriDense corn, but with greater available phosphorus content because it has less phytate phosphorus. Both experiments were conducted at a commercial swine research facility in southwest Minnesota. In Exp. 1, 1,162 gilts (initially 98.3 lb) were used in a 28-d study. Pigs were blocked by weight, and were randomly allotted to one of six dietary treatments. Pigs were fed diets based on corn-soybean meal with yellow dent (YD) or NutriDense Low Phytate corn and 0, 3, or 6% added fat, in a 2 × 3 factorial arrangement. A constant true ileal digestible (TID) lysine:energy ratio of 2.80 g TID lysine:Mcal ME was maintained in all diets, as well a constant available P:energy ratio of 0.90 g/Mcal. Overall (d 0 to 28), there were no corn source × fat content interactions (P>0.79). Regardless of corn source, ADG and F/G improved linearly (P<0.03, and P<0.01, respectively) as the amount of fat increased in the diet. There were no differences in growth performance between pigs fed diets containing NutriDense Low Phytate and those fed YD corn. In Exp. 2, a total of 1,128 gilts (initially 180.0 lb) were used in a 28-d growth assay. Pigs were blocked, and were randomly allotted to one of six dietary treatments. Pigs were fed similarly to those in Exp. 1, with diets based on corn-soybean meal, using either NutriDense Low Phytate or YD corn and 0, 3, or 6% added fat. A constant TID lysine:energy ratio of 2.15 g/Mcal ME was maintained in all diets, as well as a constant available P:energy ratio of 0.75 g/Mcal. Overall (d 0 to 28), there was a tendency for a corn source × fat content interaction for F/G (P<0.07), which was a result of pigs fed YD corn having improved F/G only at 6% added fat, whereas improvements were seen in pigs fed NutriDense Low Phytate at both 3 and 6% added fat. Also, there was an improvement in ADG (linear P<0.01) and F/G (linear, P<0.01) as the amount of fat increased in the diet, regardless of corn source. There was no difference in growth performance between pigs fed diets containing NutriDense Low Phytate and those fed YD corn. These studies indicate that increasing amounts of added fat improved growth performance, regardless of corn source. Pig growth performance is similar for pigs fed NutriDense Low Phytate corn and fed YD corn, although NutriDense Low Phytate corn does have the advantage of having higher amino acid concentrations and less phytate phosphorus.
Keywords: Pigs; Yellow dent corn; NutriDense low phytate corn; Swine